Nursing students challenges towards clinical learning environment at the school of nursing and Midwifery in Addis Ababa University. A qualitative study - Semarya Berhe; Tigistu Gebretensaye (Elsevier, 2021)
Background: Nursing is a practice based profession that is built on theoretical knowledge, both of which gained through nursing education program. Clinical learning environment component has a great role in providing students with professional abilities by combining cognitive, psychomotor and affective skills. Evidences have identified clinical learning environment as one of the key factor to achieve the desired out comes. Students often face challenges during the courses of clinical learning, which may affect their competence. The aim was to explore challenges faced by nursing students in clinical learning environment. Method: An exploratory approach qualitative method was used in Addis Ababa University, Department of Nursing in January 2018. Semi-structured data collection tool was designed to gather information from students. Final year nursing students were purposively selected and interviewed about their experiences and challenges they faced in the clinical learning environment during their stay in the school. Data was audio record, verbatim transcribed, condensed, coded and analyzed based on content analysis. The data was peer reviewed to ensure its trustworthiness. Result: The participants consisted of nine nursing students, five males and four females aged between 22 and 24 years were involved. Three major themes including Theme 1: learner's non-readiness, Theme 2: insufficient clinical supervision and Theme 3: unsupportive clinical environment were emerged. Conclusion: proper preparation of students, good selection of ideal clinical environment that fulfill the objective and adequate coaching, guidance and supervision may be necessary to enhance quality education and to produce competent nurse professionals.